Implementation of the Qardhul Hasan Agreement at Indonesian Islamic Financial Institutions - Putri Rizka Citaningati; Kamaluddin Kamaluddin; Ilham Dwitama Haeba (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
Qardhul Hasan is one of the alternatives for usury-based loans (debt). Islamic economic principles forbid a loan with interest. The aim of loan transactions through Qardhul Hasan is used to help increase the country's economic growth. This working paper aims to explain the concept of Qardhul Hasan management. The management of Qardhul Hasan can be implemented from zakat, infaq, sadaqah, and waqf funds. One of the main regulations in carrying out the management of Qardhul Hasan is the DSN-MUI Fatwa No. 19/DSN-MUI/IV/2001 concerning al-Qardh. With a descriptive qualitative approach, this study aims to explain the implementation of the Qardhul Hasan contract at BAZNAS, BWI, and other Islamic financial institutions. BAZNAS and BWI are Islamic financial institutions in Indonesia that are active in implementing Qardhul Hasan in their operational activities. Therefore, the result of this research will also explain the differences in the management of Qardhul Hasan in BAZNAS Semarang Regency and BAZNAS Tulungagung Regency. This research is necessary to do because this study provides a descriptive perspective to explain the advantages of each of these Islamic financial institutions in detail. Moreover, the result of this study would become a comparison of each of the management of these Islamic financial institutions that can be input for every other Islamic financial institution.